Compressive fatigue performance of fiber-reinforced lightweight concrete with high-volume supplementary cementitious materials. (October 2016) - Choi, Se-Jin; Mun, Jae-Sung; Yang, Keun-Hyeok; Kim, Si-Jun
Abstract: As a part of the fundamental investigation to evaluate the compressive fatigue damage of fiber-reinforced lightweight concrete using high-volume supplementary cementitious materials (SCMs), the stress–strain response of the concrete was examined under cyclic loading within maximum stress levels of 0.9, 0.8, and 0.75 f c ' and a minimum stress level fixed at 0.1 f c ', where f c ' is the concrete compressive strength. To produce a high-volume SCM binder, 20% fly ash and 50% ground granulated blast-furnace slag were used as a partial replacement for cement. Amorphous steel (AS) and polyvinyl acetate (PVA) fibers were added individually or in combination considering their conventionally recommended volume fractions. The fatigue tests were carried out by controlling the load between two limits with a sinusoidal variation at a frequency of 1 Hz. Test results showed that PVA fiber was preferable to AS fiber in enhancing the fatigue life of HVS-LWC, whereas the fatigue damage of the PVA fiber concrete was lower than that of the AS fiber concrete. This trend was more notable under a higher maximum stress level. To improve the fatigue life and fatigue damage of concrete, hybridization of both fibers rather than monolithic use is recommended.